An Analysis of Grammatical Cohesion Found in Barack Obama’s Speech - Faroz Hizbullah,; Seno H Putra,; Andi Idayani, (DISCOVERY JOURNAL, 2022)
The purpose of this research was to find out the types of grammatical cohesion devices in Barack Obama's speech Grammatical cohesion deals with grammatical and semantic connections. Grammatical cohesion belongs to the various grammatical devices that can be used to make relations between one sentence and the other sentences to be more explicit. Based on the theory by Halliday and Hassan (1976) provide the basic categories of grammatical cohesion pointing that can systematize this concept by classifying it into a small number of distinct categories. They are Reference, Substitution, Ellipsis, and Conjunction In this research, the researcher was conducted to analyze grammatical cohesion devices, especially in Barack Obama The Ex-President of US4. The research design of this research was descriptive research by using a qualitative approach. This was based on investigating involving description, calculating, and analysis. There was only one variable in the research namely Grammatical Cohesion The researcher took the data by downloading five selected episodes of speech led by Barack Obama It was about 5 appendix of trances between the Speaker and the Hearer m Barack Obama Speech in Public. The findings of this research showed that found some utterances of Barack Obama in those five chosen episodes. Based on the data analysis, there are References about 77 data. The researcher found Substitution about data of this research. Furthermore, the researcher found Elipsis about 4 data of this research. Then, Conjunction found in this research around 59 data. The most frequent strategy used by Barack Obama is References, most frequently used References and Conjunction.